Growth dynamic of biofilm-associated Naegleria fowleri in freshwater on various materials - Goudot, Sébastien; Mathieu, Laurence; Herbelin, Pascaline; Soreau, Sylvie; Jorand, Frédéric P. A. (Frontiers in Microbiology, 2024)
In industrial water systems, the occurrence of biofilm-associated pathogenic free-living amoebae (FLA) such as Naegleria fowleri is a potential hygienic problem, and factors associated with its occurrence remain poorly understood. This study was aimed at evaluating the impact of four cooling circuit materials on the growth of N. fowleri in a freshwater biofilm formed at 42 °C and under a hydrodynamic shear rate of 17 s -1 (laminar flow): polyvinyl chloride, stainless steel, brass, and titanium. Colonization of the freshwater biofilms by N. fowleri was found to be effective on polyvinyl chloride, stainless steel, and titanium. For these three materials, the ratio of [bacterial prey]/[amoeba] was found to control the growth of N. fowleri. All materials taken together a maximum specific growth rate of 0.18 ± 0.07 h -1 was associated with a generation time of about four hours. In contrast, no significant colonization of N. fowleri was found on brass, contribution of copper is therefore strongly suspected.